Penguatan Pendidikan Karakter P5 melalui Program Pemberdayaan Minat dan Bakat di PKBM Homeschooling HSPG Jember - Muhammad Hafidz Nasrullah (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
The problems faced by the HSPG Homeschooling Community Service Center (PKBM) in Jember relate to students in the Package A equivalency program, where they demonstrate deficiencies in character development. This occurs due to limited interaction between students, tutors, and the surrounding environment, which should have a positive influence on character development, such as the ability to work together and collaborate with others. The purpose of this study is to describe the strengthening of P5 character education through the interest and talent empowerment program at the HSPG Homeschooling Community Service Center in Jember. This study refers to Thomas Lickona's 1991 character education theory using a qualitative descriptive method. The research location was determined using purposive sampling, key informants were selected from two members of the empowerment program implementation team and two students using purposive sampling, and data were collected through semi-structured interviews, participant observation, and documentation. In the data analysis stage, the researcher used data collection, data reduction, data presentation, and conclusion drawing. To ensure the validity and reliability of the data, the researcher employed triangulation techniques involving sources and methods. The research results show that the empowerment program can improve students' character. This improvement is evident in the achievement of P5 character education indicators, such as the character of faith and noble morals reflected in the understanding of religious values and daily behavior. Global diversity character emerges when students demonstrate mutual respect between cultures, creating a comfortable learning environment. The character of mutual cooperation is evident in positive collaboration in groups, where they share tasks to achieve common goals. Independent character is evident in the ability to manage time and the learning process, as well as self-evaluation. Critical thinking character emerges from the ability to analyze information and distinguish fact from opinion, while creative character is demonstrated through the creation of works from their ideas. The conclusion of the research conducted is that the empowerment program implemented at PKBM Homeschooling HSPG Jember has succeeded in improving the character of Faith, piety, and noble character, global diversity, mutual cooperation, independence, critical thinking, and creativity can be seen from the behavior and attitudes of students in daily activities.
Finalisasi Repo 23 Juni 2026_Yudi
Keywords: character building; empowerment program; Homeschooling